A study on the Effects of staff separation on employees - Manaswini, M.K. (International Journal of Psychosocial Rehabilitation, 2020)
Human resource management is an essential department in an organisation which helps in maintaining relation and work balance between staff. This might be a sensitive issue which can instigate conflicts between different departments in an organisation or even between staff. The Human Resource manager has a key role to play in an organisation. In this research paper the author will take a closer look on the effects of staff separation on other employees and how it affects the organisation as a whole. In this research paper SPSS Package is used for analysis the responses collected. This aim of this research paper was to understand the present scenario of staff separation and its effects on employees.Descriptive research is used for the purpose of the study. Convenient sampling method is used to collect based on the ease of access or availability. Independent variables are Age, gender, educational qualification. Dependent variables are role of stress on staff separation on employees, effects of staff separation on existing employees and level agree ability on the reasons for staff separation. Statistical tools used are Independent sample T test, chi-square and ANOVA. Sample size is 1527. It was found from analysis that perception of reasons for staff separation varies with educational qualification of respondents and also the perception of effects of staff separation on existing employees varies with age of the respondents.